2021
DOI: 10.3389/fpsyg.2021.755220
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Life Satisfaction Among Middle-Aged and Older Adults: Mediation Effect of Functional Disability

Abstract: With increasing age, middle-aged and older persons face a series of physical and mental health problems. This study aimed to explore the latent relationships among age, functional disability, depression, and life satisfaction. The data were obtained from the Wave 2 (in 2013–2014) and Wave 3 (in 2015–2016) surveys of the China Health and Retirement Longitudinal Study. The analytic sample in the present study included 15,950 individuals aged 45 years and over. The participants answered the same questions concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 75 publications
3
12
0
Order By: Relevance
“…This study also found that the depressive symptoms of adolescents persist in time, which is consistent with the previous research results ( Lee et al, 2020 ; Li et al, 2021 ). That is to say, Depression of adolescents in 2017–2018 will affect depression in 2019–2020 to a certain extent.…”
Section: Discussionsupporting
confidence: 93%
“…This study also found that the depressive symptoms of adolescents persist in time, which is consistent with the previous research results ( Lee et al, 2020 ; Li et al, 2021 ). That is to say, Depression of adolescents in 2017–2018 will affect depression in 2019–2020 to a certain extent.…”
Section: Discussionsupporting
confidence: 93%
“…For example, previous studies have shown that older people with limited social support are vulnerable to psychological problems, such as depression and anxiety (21,22). Although previous studies have indicated the association between disability, social support, and depressive symptoms (20,23,24), few studies have discussed the potential role of social support in assessing the association between disability and depressive symptoms. A study indicated that social networks with sufficient scale, quality, and interaction frequency will give the elderly a feeling of being valued and loved (25).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, high grit will reduce the level of depression. Previous studies have found that depression has a strong impact on individual life satisfaction ( 28 , 47 ). In summary, during the period of recurrent outbreak of COVID-19, grit not only directly affected life satisfaction but also indirectly affected college students' life satisfaction by affecting college students' depression.…”
Section: Discussionmentioning
confidence: 99%